Revisit: Lifestyle of brand awareness and taste quality with moderation of experience quaity - Puput Albahiyah; Surya Bintarti; Taufiq Rachman (Junal Ilmu Manajemen, 2023)
This study reviews Revisit: Lifestyle Brand Awareness and Taste Quality with Moderation of Experience Quality in Bekasi Regency Area. This study aims to illustrate the existence of a lifestyle by drinking nestle pure life mineral water that is good for health and for a quality of brand awareness. Nestle pure life mineral water which is industrialized in Indonesia was established in 1985 with PT. Akasha Wira International Tbk. with the presence of mineral water in hygienic and instant packaging, it is easy to carry anywhere that is in great demand and is believed to have healthy water quality and feels light to drink. This study used quantitative methods with primary data collected by isendental sampling techniques or proposive sampling with the distribution of questionnaires through google forms and non-probality sumpling population types that had more then 100 respondents who met the criteria. Has six hypotheses formulated one of them has one that is not significant and tested regression analysis which is processed using test instruments with the help of pls software that produces validity and reliability with decent results.